Utilization of cytoreductive nephrectomy and patient survival in the targeted therapy era. Issue 9 (4th November 2013) - Conti, Simon L.; Thomas, I‐Chun; Hagedorn, Judith C.; Chung, Benjamin I.; Chertow, Glenn M.; Wagner, Todd H.; Brooks, James D.; Srinivas, Sandy; Leppert, John T.
<x xml:space="preserve">Abstract</x> We sought to analyze utilization and survival outcomes of cytoreductive nephrectomy (CN) in patients with metastatic renal cell carcinoma (RCC) before and after introduction of targeted therapy. We identified patients with metastatic RCC between 1993 and 2010 in the SEER registry and examined temporal trends in utilization. We performed a joinpoint regression to determine when changes in utilization of CN occurred. We fitted multivariable proportional hazard models in full and propensity score‐matched cohorts. We performed a difference‐in‐difference analysis to compare survival outcomes before and after introduction of targeted therapy. The proportion of patients undergoing CN increased from 1993 to 2004, from 29% to 39%. We identified a primary joinpoint of 2004, just prior to the introduction of targeted therapy. Beginning in 2005, there was a modest decrease in utilization of CN. CN was associated with a lower adjusted relative hazard (0.41, 95% confidence interval 0.34–0.43). Median survival among patients receiving CN increased in the targeted therapy era (19 vs. 13 months), while median survival among patients not receiving CN increased only slightly (4 vs. 3 months). Difference‐in‐difference analysis showed a significant decrease in hazard of death among patients who received CN in the targeted therapy era. Despite decreased utilization in the targeted therapy era, CN remains associated with improved survival. Prospective randomized trials are needed to confirm the benefit of CN among patients with metastatic RCC treated with novel targeted therapies.